2018
DOI: 10.1111/jcpt.12711
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hypothermia treatment on gentamicin pharmacokinetics in neonates with hypoxic-ischaemic encephalopathy: A systematic review and meta-analysis

Abstract: Gentamicin clearance is decreased in neonates with HIE receiving hypothermia treatment compared to those not receiving hypothermia treatment. Modified gentamicin dosing regimens are required to avoid potential toxicity related to higher concentrations during hypothermia treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 39 publications
0
8
0
1
Order By: Relevance
“…Amikacin clearance was decreased to 40.6% in these neonates and a 12-h increase in the amikacin dosing interval was proposed to correct for the reduced clearance [133]. A decreased clearance of gentamycin during TH was confirmed by a meta-analysis of eight studies: modified gentamicin dosing regimens with 36-h intervals are required to yield safe and effective exposures [134]. Considering reduced drug clearance, Cies et al suggested that dosing regimens of ampicillins 25-50 mg/kg/day were sufficient to protect against susceptible bacteria in neonates with HIE [135].…”
Section: Tdm and Antiepileptic Drugsmentioning
confidence: 94%
“…Amikacin clearance was decreased to 40.6% in these neonates and a 12-h increase in the amikacin dosing interval was proposed to correct for the reduced clearance [133]. A decreased clearance of gentamycin during TH was confirmed by a meta-analysis of eight studies: modified gentamicin dosing regimens with 36-h intervals are required to yield safe and effective exposures [134]. Considering reduced drug clearance, Cies et al suggested that dosing regimens of ampicillins 25-50 mg/kg/day were sufficient to protect against susceptible bacteria in neonates with HIE [135].…”
Section: Tdm and Antiepileptic Drugsmentioning
confidence: 94%
“…extraction ratio) characteristics (Pokorna et al, 2015;Zeilmaker et al, 2018). This is also reflected in Table 1, in which a lower gentamicin (Choi et al, 2018) or amikacin (Cristea et al, 2017) clearance is related to TH and/or PA (−31%, −40.6%), with an increase in clearance (+29%) over time (after TH, highly correlated with increasing PNA) (Bijleveld et al, 2016), and weight and/or creatinine as covariates (Frymoyer et al, 2013;Cristea et al, 2017). A similar pattern can be observed for different b-lactam antibiotics (ampicillin, amoxicillin, benzyl-penicillin) with reduced clearance during controlled hypothermia (−66%) (Cies et al, 2017) and a subsequent increase in clearance (+58%) over time (Bijleveld et al, 2018).…”
Section: Knowledge On the Impact Of Hypothermia On Adme Processes In mentioning
confidence: 52%
“…Finally, hypothermia reduces renal drug excretion. For drugs eliminated by glomerular filtration rate (GFR) in neonates with PA and TH, studies consistently showed that elimination is significantly (−30 up to −40%) reduced, with an increase after finalization of the TH (> 72h) (Mark et al, 2013;Ting et al, 2015;Bijleveld et al, 2016;Cristea et al, 2017;Choi et al, 2018). A similar pattern can be observed for the different b-lactam antibiotics (ampicillin, amoxicillin, benzyl-penicillin).…”
Section: Knowledge On the Impact Of Hypothermia On Adme Processes In mentioning
confidence: 66%
“…14,[23][24][25][26][27][28] A recent metaanalysis reported that CL of gentamicin was reduced during TH. 29 In this study, they have summarized the results from the published studies and reported reduced CL of gentamicin during TH. They focused on the combined impact of PA and TH.…”
Section: Discussionmentioning
confidence: 99%